2018
DOI: 10.1088/1742-6596/1125/1/012018
|View full text |Cite
|
Sign up to set email alerts
|

The effects of non-uniform drive on plasma filaments

Abstract: Wendelstein 7-X core fueling is primarily achieved through pellet injection. The trajectory of plasmoids from an ablating pellet is an ongoing research question, which is complicated by the complex magnetic geometry of W7-X; curvature drive varies significantly toroidally, including a change in the drift drive direction. Here we use the Hermes model in BOUT++ to simulate cold plasma filaments in slab geometries where the magnetic drift drive is non-uniform along the field line. It is shown that if the field-li… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 12 publications
3
13
0
Order By: Relevance
“…A filament dipole -and therefore the electric field which drives motion -is created due to diamagnetic drifts (curvature and ∇B). Acknowledging previous work (Shanahan et al 2018) which indicated that this curvature drive could be approximated as an average curvature, we see that the large aspect ratio of Wendelstein 7-X leads to a small polarizing force. This effect is somewhat mitigated by the large connection lengths of the W7-X island divertor topology.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…A filament dipole -and therefore the electric field which drives motion -is created due to diamagnetic drifts (curvature and ∇B). Acknowledging previous work (Shanahan et al 2018) which indicated that this curvature drive could be approximated as an average curvature, we see that the large aspect ratio of Wendelstein 7-X leads to a small polarizing force. This effect is somewhat mitigated by the large connection lengths of the W7-X island divertor topology.…”
Section: Discussionsupporting
confidence: 70%
“…Simulations of blobs in slab geometries are common (D 'Ippolito & Myra 2003;D'Ippolito et al 2004;Aydemir 2005;Garcia et al 2005;Garcia, Bian & Fundamenski 2006;Myra, Russell & D'Ippolito 2006;Riva et al 2016;Shanahan & Dudson 2016;Walkden et al 2016) since these simulations are much faster than global edge simulations, allowing thorough investigations of the primary mechanisms in filament dynamics. This method has already been applied to non-uniform drive scenarios (Shanahan, Dudson & Hill 2018), a feature which is prominent in -but not exclusive to -stellarators. In Shanahan et al (2018) it was determined that a filament which is driven by non-uniform curvature will, on average, propagate as if driven by the field-line-averaged curvature -except in cases of highly non-uniform drive.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the normal curvature in W7-X has strong, fine-scale variations along a magnetic flux tube [14,28], previous work has indicated that due to the fast dynamics parallel to the ambient magnetic field, the averaged normal curvature along a field line dominates the formation and behaviour of turbulent filaments [14,29]. Since the magnetic configurations of W7-X considered here mostly differ with respect to the rotational transform, the magnetic curvature profile along a field line starting from the probe does not change more than a few % between configurations.…”
Section: Magnetic Field Characteristicsmentioning
confidence: 99%
“…Such environment for filaments is just starting to be addressed with simulations [10]. Numerical studies [11] claim that filaments can exist and propagate outward in the presence of a nonuniform curvature drive as long as the field-line averaged curvature is negative. This behaviour is enabled by the high conductivity along the field lines which effectively averages polarization.…”
Section: Introductionmentioning
confidence: 99%